Development of Mufrodat E-Modules Based on Isyaroh and Local Wisdom to Improve Arabic Text Comprehension - Fairus, Nafa Afida; Muljani, Sutji; Suriswo, Suriswo (Universitas Pahlawan Tuanku Tambusai, 2025)
Mastery of vocabulary is an important key in learning Arabic, because it plays a significant role in the development of four language skills (Maharoh Al-Lughawiyyah): listening (Maharoh Al-Istima'), reading (Maharoh Al-Qiroah), speaking (Maharoh Al-Kalam), and writing (Maharoh Al-Kitabah). However, the availability of printed books for Arabic subjects at MAN 2 Tegal is inadequate, and learning still uses conventional methods without the support of learning media. This condition causes low student understanding. To overcome these problems, this study aims to develop learning media based on valid, practical, and effective vocabulary e-modules. This study involved 128 students with a sample of 64 students in grades XI IPA 1 and XI IPA 2 who were selected using a purposive sampling technique. The results of the study showed that: (1) The vocabulary e-module was considered very valid by subject teachers, material validators, and media validators; (2) The level of practicality of the e-module based on student responses reached (90%), which was categorized as practical to very practical; (3) The effectiveness of the e-module is proven by the results of the Gain Score test with an average increase of 0.758, which is included in the high category. Thus, the Mufrodat e-module has the potential to be a solution to significantly improve students' understanding of Arabic.